2016
DOI: 10.1590/s1414-40772016000200011
|View full text |Cite
|
Sign up to set email alerts
|

A inclusão de universitários com deficiência em cursos de Educação Física na cidade de Maceió/AL

Abstract: A inclusão de universitários com deficiência em cursos de Educação Física na cidade de Maceió/AL jurídico DOI: http://dx.doi.org/10.1590/S1414-40772016000200011 A inclusão de universitários com deficiência em cursos de Educação Física na cidade de Maceió/AL David dos Santos Calheiros Neiza de Lourdes Frederico FumesResumo: Nos anos mais recentes, uma crescente participação de pessoas com deficiência a ter acesso à Educação Superior. Esse processo desafia e provoca mudanças dentro e fora dos muros das Instituiç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
1
0
9
Order By: Relevance
“…In the SciELO platform, 39 published studies were found with themes related to accessibility and/or inclusion in higher education. Within this theme, the studies focused on different specificities: teacher training to attend students with disabilities in higher education (Reis, Eufrásio and Bazon, 2010); the right to inclusion in higher education (Araujo, 2017); inclusion specifically of students with visual disabilities (Fernandes and Costa, 2015;Regiani and Mól, 2013); inclusion and accessibility specifically of students with hearing disabilities (Bisol et al, 2010;Fernandes and Moreira, 2017;Martins and Napolitano, 2017;Mesquita, 2018); inclusion in higher education (Almeida and Ernica, 2015;Calheiros and Fumes, 2016;Facci, Silva and Souza, 2018;Nozu, Bruno and Cabral, 2018;Oliveira, Gonçalvez and Oliveira, 2016;Poker, Valentim and Garla, 2018); normalization, access legitimacy, participation, and formation (Cabral and Melo, 2017); accessibility in higher education (Silva and Ferreira, 2017); permanence of students with disabilities (Maciel and Anache, 2017); admission and permanence (Castro and Almeida, 2014;Moreira, Bolsanello and Seger, 2011); accessibility and permeance (Garcia, Bacarin and Leonardo, 2018); centers of accessibility in the universities (Ciantelli andLeite, 2016;Ciantelli, Leite and Nuernberg, 2017;Melo and Araújo, 2018); attention to diversity in higher education (Martos-García and Valencia-Peris, 2016); mapping of students in special education (Lourenço and Battistella, 2018); survey on the number of PWD enrolled in higher education (Duarte et al, 2013); participation of students with disabilities in higher education (Gesser and Nuernberg, 2017); meanings of inclusion through students' perspectives (Almeida and Ferreira, 2018); satisfaction evaluation of students with disabilities (Guerreiro, Almeida and Silva Filho, 2014;...…”
Section: Introductionmentioning
confidence: 99%
“…In the SciELO platform, 39 published studies were found with themes related to accessibility and/or inclusion in higher education. Within this theme, the studies focused on different specificities: teacher training to attend students with disabilities in higher education (Reis, Eufrásio and Bazon, 2010); the right to inclusion in higher education (Araujo, 2017); inclusion specifically of students with visual disabilities (Fernandes and Costa, 2015;Regiani and Mól, 2013); inclusion and accessibility specifically of students with hearing disabilities (Bisol et al, 2010;Fernandes and Moreira, 2017;Martins and Napolitano, 2017;Mesquita, 2018); inclusion in higher education (Almeida and Ernica, 2015;Calheiros and Fumes, 2016;Facci, Silva and Souza, 2018;Nozu, Bruno and Cabral, 2018;Oliveira, Gonçalvez and Oliveira, 2016;Poker, Valentim and Garla, 2018); normalization, access legitimacy, participation, and formation (Cabral and Melo, 2017); accessibility in higher education (Silva and Ferreira, 2017); permanence of students with disabilities (Maciel and Anache, 2017); admission and permanence (Castro and Almeida, 2014;Moreira, Bolsanello and Seger, 2011); accessibility and permeance (Garcia, Bacarin and Leonardo, 2018); centers of accessibility in the universities (Ciantelli andLeite, 2016;Ciantelli, Leite and Nuernberg, 2017;Melo and Araújo, 2018); attention to diversity in higher education (Martos-García and Valencia-Peris, 2016); mapping of students in special education (Lourenço and Battistella, 2018); survey on the number of PWD enrolled in higher education (Duarte et al, 2013); participation of students with disabilities in higher education (Gesser and Nuernberg, 2017); meanings of inclusion through students' perspectives (Almeida and Ferreira, 2018); satisfaction evaluation of students with disabilities (Guerreiro, Almeida and Silva Filho, 2014;...…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores trazem, no corpo do seu texto, relatos de ingressantes com deficiência sobre a acessibilidade. [13][14][15] Um estudo explicita que as pessoas que solicitaram atendimento especial nas provas de ingresso foram atendidas cada uma em sua especificidade, não havendo maiores problemas na realização dos exames. 13 Dessa forma, pôde-se verificar que, em algumas instituições, os alunos com deficiência obtêm êxito ao solicitar atendimento especial, fator esse que auxilia diretamente o melhor acesso do indivíduo no Ensino Superior, visto que são disponibilizados recursos para que estes executem a prova de forma plural.…”
Section: Discussionunclassified
“…Muitas vezes, o aluno, já matriculado, não tem o profissional para ajudá-lo, sendo necessário o uso da força da lei para tal. 14 Além das falas dos discentes com deficiência, também há fragmentos dos autores que relatam a insatisfação dos alunos nas questões pedagógicas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Na análise das entrevistas, pela técnica análise de conteúdo, foi possível notar um descompasso entre o discurso dos coordenadores com o dos estudantes participantes, pois enquanto os primeiros relatavam a oferta de condições e recursos específicos, os estudantes apontavam que a permanência no ensino superior estava condicionada mais ao esforço pessoal atrelado ao auxílio dos colegas da turma, situações identificadas como favorecedoras para que pudessem acompanhar as atividades acadêmicas, ao invés de ajustes e/ou provimentos institucionais. O estudo concluiu que a "[...] participação desse público na educação superior estava ainda muito condicionada às suas capacidades de adaptação a ambientes não inclusivos" (CALHEIROS;FUMES, 2016, p. 536).…”
Section: Mapeamento E Trajetória De Pessoas Com Deficiência No Ensinounclassified